Transition from school to adult services for young people with severe or profound intellectual disability: A systematic review utilizing framework synthesis. Issue 6 (22nd June 2018) - Jacobs, Paula; MacMahon, Kenneth; Quayle, Ethel
Abstract : Background: The transition to adulthood has been described as a difficult time in the lives of young people with intellectual disability. There has been little emphasis on young people with severe or profound intellectual disability specifically, even though their pathways may differ, due to greater support needs across the life course. Methods: A systematic review was conducted utilising Bronfenbrenner's ecological model to inform framework analysis to synthesise qualitative findings. Results: Taking an ecological perspective proved valuable. The transition process was described as stressful and barriers were identified across the ecological levels. Parents accounted for the majority of participants in studies, and the needs of young people and their parents emerged as highly interdependent. Conclusion: Themes reflect the complex nature of the question what adulthood should look like for individuals with severe or profound intellectual disability. There is a lack of involvement of multiple stakeholders and young people themselves within studies.